Developing and managing electronic collections : the essentials - Johnson, Peggy, 1948- (ALA Editions, 2013)
The complex issues associated with developing and managing electronic collections deserve special treatment, and library collection authority Peggy Johnson rises to the challenge with a book sure to become a benchmark for excellence. Providing comprehensive coverage of key issues and decision points, she offers advice on best practices for developing and managing these important resources for libraries of all types and sizes.